(untitled) (Global Journal of Management and Business Research, 2012)
Quality of work life is a critical concept with having lots of importance in employee#x2019;s life. Quality of work life indicates a proper balance both in work and personal life which also ensure organizational productivity and employee#x2019;s job satisfaction. This research study attempted to find out the factors that have an impact and significance influence on quality of work life of employees in private limited companies of Bangladesh. To begin with the factors are identified through literature review and current context of Bangladesh. Seven factors were found and a quantitative research was done. After developing a questionnaire, survey was conducted among 100 employees. The outcome of the research is that six out of seven factors (work load, family life, transportation, compensation policy and benefits, working environment, working condition and career growth) have significant influence on quality of work life. The study concluded that an appropriate organization culture, compensation policy, career growth and relative facilities can leads to a satisfied employee mindset which ensure the overall organization productivity.